2020
DOI: 10.1111/anae.15339
|View full text |Cite
|
Sign up to set email alerts
|

PROSPECT guideline for elective caesarean section: updated systematic review and procedure‐specific postoperative pain management recommendations

Abstract: Caesarean section is associated with moderate-to-severe postoperative pain, which can influence postoperative recovery and patient satisfaction as well as breastfeeding success and mother-child bonding. The aim of this systematic review was to update the available literature and develop recommendations for optimal pain management after elective caesarean section under neuraxial anaesthesia. A systematic review utilising procedure-specific postoperative pain management (PROSPECT) methodology was undertaken. Ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
158
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(221 citation statements)
references
References 169 publications
(390 reference statements)
6
158
0
14
Order By: Relevance
“…Recently, Abdel Shaheed analyzed data from 36 publications and reported that paracetamol produced modest pain relief in hip and knee osteoarthritis, tension headache, and post-craniotomy pain and that it was ineffective in other conditions [ 145 ]; the authors concluded with the need for large, high-quality trials to reduce uncertainty about the efficacy of paracetamol in common pain conditions. In the last few months, new published studies report the safe use of paracetamol in patients with chronic kidney disease [ 147 ], the significant efficacy of paracetamol for post-arthroplasty pain [ 148 ], the lesser efficacy of paracetamol than ibuprofen for post-laminectomy pain [ 149 ], the opioid-sparing effects of paracetamol in the Emergency Department [ 150 ], the recommendations against paracetamol in lumbar spinal stenosis with neurogenic claudication [ 151 ], and the recommendations in favor of paracetamol for postcesarean pain [ 152 ] and for migraine [ 153 , 154 ].…”
Section: Recent Findings and Future Directionsmentioning
confidence: 99%
“…Recently, Abdel Shaheed analyzed data from 36 publications and reported that paracetamol produced modest pain relief in hip and knee osteoarthritis, tension headache, and post-craniotomy pain and that it was ineffective in other conditions [ 145 ]; the authors concluded with the need for large, high-quality trials to reduce uncertainty about the efficacy of paracetamol in common pain conditions. In the last few months, new published studies report the safe use of paracetamol in patients with chronic kidney disease [ 147 ], the significant efficacy of paracetamol for post-arthroplasty pain [ 148 ], the lesser efficacy of paracetamol than ibuprofen for post-laminectomy pain [ 149 ], the opioid-sparing effects of paracetamol in the Emergency Department [ 150 ], the recommendations against paracetamol in lumbar spinal stenosis with neurogenic claudication [ 151 ], and the recommendations in favor of paracetamol for postcesarean pain [ 152 ] and for migraine [ 153 , 154 ].…”
Section: Recent Findings and Future Directionsmentioning
confidence: 99%
“…In the recently published PROSPECT guideline, the use of fascial plane blocks such as QLB is recommended when intrathecal morphine is not used in CD. 37 The low pain scores and opioid consumption in both blocks, as well as the absence of complications, will contribute to its more significant involvement in postoperative pain management in daily practice. Our study was performed in spinal anaesthesia patients and showed that the QLB-III block is superior to QLB-II.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Although CS has some benefits, such as lowering the risk of birth injuries (eg, asphyxia, shoulder dystocia, fractures 2 ), it can cause moderate to severe postoperative pain. 3 This pain must be taken seriously and treated in a timely manner because it may delay recovery, affect daily activities, and impact maternal psychological well-being. 4 Furthermore, insufficient treatment may cause pain to become persistent 5 and chronic.…”
Section: Introductionmentioning
confidence: 99%